The Effect of Self Hypnosis on the Reduction of Anxiety of Pregnant Women in Trimester III Practice Midwife Anni Rizkiah - Siregar , Nurelilasari; Batubara, Rini Amalia; Pohan, Sakinah Yusro (International Journal of Public Health Excellence (IJPHE), 2022)
The purpose of this study was to identify the characteristics of pregnant women in the third trimester, identify the anxiety of pregnant women before and after self hypnosis and to find out the effect of self hypnosis on reducing anxiety in third trimester pregnant women, this research method is a quasi experiment, with a one-group pre-test and post-test design. The samples taken were 15 pregnant women. Sampling in this study using the Total Sampling method . Data was collected through a check list observation sheet and analyzed univariately and bivariately with the Wilcoxon test and presented in the form of a frequency distribution table. Results of this study the value of is 0.01 ( ρ < 0.05). The conclusion of this study states that there is an effect of self hypnosis on the anxiety of pregnant women in the third trimester at the Midwife Anni Rizkiah Practice, Sitampa Simatoras Village, South Tapanuli. Researcher Suggestions It is hoped that the midwives who drive the practice will make policies related to self-hypnosis to be taught to every pregnant woman who visits. Throughout the pregnancy process, the mother will remain calm and relaxed. Mother and baby are healthy with normal delivery.